Complete chloroplast genome sequence and phylogenetic analysis of Symphytum officinale - Yuemei Zhao; Xiaodan Chen; Tao Zhou; Rongxiang Zhang; Fang Zhao; Xiao Zhang (Genetics and Molecular Biology)
Abstract Symphytum officinale is a perennial herb belonging to the Boraginaceae. Here, we sequenced the complete chloroplast (cp) genomes of S. officinale using Illumina sequencing technology. The results revealed that the cp genome is 148,149 bp in length and exhibits a typical quadripartite structure, with a pair of inverted repeat regions (IR) comprising 27,001 bp, a large single-copy (LSC) region comprising 77,366 bp, and a small single-copy (SSC) region comprising 16,781 bp. The sequence contained 133 unique genes, including 86 protein-coding genes, 37 transfer RNAs, eight ribosomal RNAs, and two pseudogenes. Six tandem, 42 dispersed, and 38 simple sequence repeats were identified. Sequence divergence analysis across 21 Boraginaceae species revealed that the most divergent regions, potentially serving as specific DNA barcodes, were found in non-coding spacers. A comparative analysis of the IR/SC boundary regions of the 21 Boraginaceae species revealed IR expansion events in S. officinale. Phylogenetic analysis based on 63 protein-coding genes demonstrated that S. officinale was closely related to Nonea vesicaria. This represents the first cp genome sequenced in Symphytum, and our results provide valuable genetic information for future population and phylogenetic studies of Boraginaceae.